Mengukur Potensi Financial Distress Dengan Melihat Pengaruh Rasio Keuangan Dan Ukuran Perusahaan - Musdalifah, Musdalifah; Saputra, Afdal Jaya (Jurnal Ilmiah Bongaya, 2021)
Abstract : This studi aim to determine whether financial ratious aand compani size affect financiial distrees in manufacturing companis listed in the Indonesian Stock Exchage. Data collection using secondary data obtained from the STIEM Bongaya Makassar Investment Gallery using purposive sampling technique. The population is manufacturin companis in the basic indusry and cemichal sector, amounting to 70 companies, while the samples taken are 10. The results of the data are normality test, multicolonierity test, heterekedessity test. Methods of data analisys using multiple linier regresion with the help of SPSS 22 software.The resuls showead that the liquiidity ratio and the sovency ratio had a positive and significan effect in financial distress. Meanwhile, the profitability ratio is rejected because the results show thaat the profitability ratio his no efect on financial distres. The result showed the proposad hipothesis test was accept because it showead a negative hipothesis test results. This mens the size of the company has no effect on finacial distress.